Acute Decompensated Heart Failure: Current Role of Diuretics and Ultrafiltration - Dea Arie Kurniawan; Indra Prasetya; Sasmojo Widito; Heny Martini (Heart Science Journal, 2023)
Acute decompensated heart failure (ADHF) continues to be the leading cause of hospitalization and has a poor prognosis. Loop diuretic had been long used as cornerstone therapy for congestion and volume overload. However, several factors including diuretic resistance and declining renal function reduced the loop diuretic's effectiveness, necessitating a different treatment strategy. In ADHF, ultrafiltration (UF) could be a promising method to volume management. UF appears to be more effective at removing fluid than diuretics, according to several studies, with better quality of life and lower rehospitalization. This review highlights the current state of knowledge regarding the use of diuretics and UF in ADHF patients, as well as the challenges and questions raised associated with each approach.